The UWB-OFDM Channel Analysis in Frequency (2009)
In this paper, the ultra-wideband channel with orthogonal frequency division multiplexing (UWB-OFDM) is analyzed in the frequency domain. For UWB-OFDM channels with log-normal fading in the time domain, we show that the amplitude of each subcarrier can be approximated by a Nakagami-m random variable, where the fading parameter, the mean power and the correlation coefficient are expressed in terms of the following parameters: time arrival of the clusters, inter-arrival time of rays inside clusters, and power decay constants of rays and clusters.